Revitalisasi Media Pembelajaran: Transformasi Membaca Permulaan di Sekolah Dasar - Elitasari, Handara Tri; Dwidarti, Fera (Paedagogie, 2026)
Early reading ability is a fundamental skill that elementary school students need to support their literacy development in later stages. However, early reading instruction still faces several challenges, particularly the low reading skills of students and the limited use of engaging instructional media. This study aims to analyze the revitalization of learning media in transforming early reading instruction for elementary school students. This research employed a mixed-method approach with data collected through observation, interviews, and questionnaires. Data were analyzed using descriptive statistics and qualitative analysis, which were then integrated to obtain a comprehensive understanding of the findings. The results show that most students are not yet able to read fluently, have difficulty with accurate pronunciation, and demonstrate low confidence when reading. Early reading instruction is still dominated by the use of textbooks, while the availability of learning media remains limited. In addition, students show strong interest in learning media that are interactive, game-based, visually appealing, colorful, and contain clear and readable letters. These findings highlight the importance of revitalizing learning media that align with students’ characteristics to support more effective early reading instruction